Synoptic Features of August Heavy Rainfall Episodes Accompanied By a Quasi-Stationary Front Over the Korean Peninsula and Its Relationship With the Western Pacific Subtropical High - Shin, Uju; Park, Sang-Hun; Yun, Yong-Ro; Oh, Chimook (Frontiers in Earth Science, 2022)
In this study, we investigated the synoptic features of the August 26–27, 2018 heavy rainfall episode, which was accompanied by a quasi-stationary front over the Korean peninsula, as well as its relationship with the climatological characteristics of the Western Pacific Subtropical High (WPSH), using reanalysis and observational data. Through a case study, we analyzed the synoptic environment and frontal structure of the heavy rainfall event by comparing it with a heavy rainfall event associated with a quasi-stationary front that occurred on June 26–27, 2018 (during the Changma period). The case study indicates that the environment and structure of the quasi-stationary fronts in both events exhibited common characteristic features: an extended WPSH and strong low-level winds along the western or northwestern edge of the WPSH and a northward tilted frontal structure. Although differences in the moisture transport path were observed (southwesterly for the Changma event and southerly for the August event), their contributions to maintaining the quasi-stationary fronts were comparable around the Korean peninsula. We further investigated the climatological characteristics of these two heavy rainfall episodes for a 30 year period (1990–2019). We identified heavy rainfall days similar to those of the case study using pattern correlations of the 850 hPa geopotential height anomaly. The occurrence frequencies for each period indicate that the environmental features of the Changma event can be regarded as the typical heavy rainfall environment during the Changma period, whereas the environmental features of the August event were not typical for heavy rainfall during August. The main difference between similar and different cases to the August event is the expansion of the WPSH. Analysis of the relationship between annual variations in the WPSH indices and the occurrence frequency of heavy rainfall days during each August period also indicates that heavy rainfall with a quasi-stationary front similar to the August event is closely related to WPSH expansion.